The post-Jaramillo persistence of Sus strozzii (Suidae, Mammalia) in Europe: New evidence from the Vallparadís Section (NE Iberian Peninsula) and other coeval sites. (1st April 2020) - Cherin, Marco; Alba, David M.; Crotti, Marco; Menconero, Sofia; Moullé, Pierre-Élie; Sorbelli, Leonardo; Madurell-Malapeira, Joan
Abstract: The Vallparadís composite section (VCS) includes the nearby paleontological sites of Cal Guardiola and Vallparadís Estació (Vallès-Penedès Basin, northeastern Iberian Peninsula). The section spans from before the Jaramillo subchron to the early Middle Pleistocene (ca. 1.2–0.6 Ma). In this study, we describe the suid record from VCS and we review those from several other European sites, in order to refine the taxonomic identity and chronostratigraphic range of Quaternary suids in Europe. The VCS sample includes a nearly complete skull, several teeth, and postcranial elements, and stands out as the richest European suid collection from the latest Early Pleistocene. Suid remains have been unearthed from both Cal Guardiola and Vallparadís Estació layers, whose age spans from the Jaramillo subchron (ca. 1.07–0.99 Ma; MIS31) to post-Jaramillo time (ca. 0.86 Ma; MIS21). Several craniomandibular and dental morphological features support an attribution to Sus strozzii . These features include a low and very deep preorbital fossa, a narrow nuchal crest, a well-developed longitudinal swelling in the middle of the mandibular corpus, the presence of styles/stylids in the upper/lower premolars, and especially the "verrucosic" morphology of the lower canine. The attribution to S. strozzii is also sustained by a cladistic analysis. These results provide interesting clues on the chronological occurrence of Quaternary suids. Sus strozzii is relatively common in Europe during the middle and early late Villafranchian (ca. 2.5–1.8 Ma), but it almost completely disappears during the latest Villafranchian (ca. 1.8–1.2 Ma). During and slightly after the Epivillafranchian (ca. 1.2–0.8 Ma), S. strozzii reappears in Europe although with relatively small samples, at VCS and several other sites including Untermassfeld (Germany; ca. 1.0 Ma), Le Vallonnet (France; ca. 1.2–1.1 Ma), Taman Peninsula (Russia; ca. 1.1–0.8 Ma), Arda River (Italy; ca. 0.99 Ma), and Slivia (Italy; ca. 0.8 Ma), among others. Consequently, in contrast to previous knowledge, we conclude that (1) S. strozzii survived in Europe (or returned there with a second dispersal event from Asia during the Epivillafranchian) at least until the end of the Early Pleistocene and (2) the arrival of Sus scrofa into that continent is not older than the Early-Middle Pleistocene boundary. Highlights: We analyze the Sus sample from the Vallparadís composite section. It is the richest European suid collection from the latest Early Pleistocene. The sample is referred to Sus strozzii Forsyth-Major, 1881 The samples from other Epivillafranchian sites can be referred to the same species. S. scrofa replaced S. strozzii not before the Early-Middle Pleistocene boundary.